PENGARUH BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA PEGAWAI UPTD PUSKESMAS LUAHAGUNDRE MANIAMOLO - Erika, Erika Putri Anjelika Dakhi (Jurnal Ekonomi dan Bisnis Nias Selatan, 2022)
The purpose of this study was to determine the Influence of Organizational Culture on the Work Discipline of UPTD Puskesmas Luahagundre Maniamolo Employees. The type of research is a quantitative type that is causal, the source of data is primary data, namely questionnaires to employees, with the population and sample in this study are employees at UPTD Luahagundre Maniamolo Health Center as many as 31 people. Data collection techniques are interview techniques, questionnaire techniques and documentation techniques. The data analysis method used is simple regression analysis. Based on the results of the hypothesis testing study with a calculated value of 1,954>ttable 1,699 so that researchers can conclude that there is an Influence of Organizational Culture on the Work Discipline of UPTD Employees of the Luahagundre Maniamolo Health Center. The suggestions of this research are It is expected that the leadership of UPTD Luahagundre Health Center to set clear and measurable work standards, and evaluate employee performance regularly. Provide training and resources needed to assist employees in achieving organizational goals. Maintain a culture that respects and values employees and their work, and provides responsibilities that are in accordance with employee competencies and abilities.